Molecular biology of the cell - Alberts, Bruce; Alberts, Bruce; Johnson, Alexander; Lewis, Julian; Morgan, David; Raff, Martin; Roberts, Keith; Walter, Peter (New York, Garland Science, 2015)
Never HIGHLIGHT a Book Again! Includes all testable terms, concepts, persons, places, and events. Cram101 Just the FACTS101 studyguides gives all of the outlines, highlights, and quizzes for your textbook with optional online comprehensive practice tests. Only Cram101 is Textbook Specific. Accompanies: 9780815344643. This item is printed on demand.
Glossary G1-G34p.; Index I1-I53p.
Keywords: Cell signalling; Cytoskeleton; Pathogens and infection; Visualizing cells